Cosmos Caudatus: A Possible Drug Candidate for Oral Squamous Cell Carcinoma - Ahmed, Alhakam A.; Shahidan, Wan Nazatul. Shima (Current Bioactive Compounds, 2021)
Oral squamous cell carcinoma (OSCC) is considered the most common neoplasm of the oral cavity and ranked the sixth most prevalent cancer worldwide. Risk factors correlated with the disease are smoking and alcohol drinking as well as HPV-16 infection. Bioactive compounds such as ascorbic acid, quercetin, kaempferol, chlorogenic acid, caffeic acid, ferulic acid, anthocyanins, and β-carotene are authenticated and shown to possess anti-oral cancer activity. Not to mention, anti- oxidant, anti-inflammatory, anti-oxidant, anti-viral, psychostimulant activities, and anti-carcinogenic effects. All of the referred constituents are abundantly found in a plant called Ulam raja, scientifically known as Cosmos caudatus (C. caudatus). C. caudatus is a plant traditionally used in Southeast Asia as an anti-diabetic, anti-arthritic, and anti-hypertensive remedy. This paper describes the substances of C. caudatus that have anti- oral cancer properties. Their properties, mechanism of action, and their most notable bioactive constituents against OSCC and their potential as chemotherapeutic drugs are discussed in this paper.
Keywords: Oral squamous cell carcinoma